The Consumer Satisfaction of Internet Service Providers in Kathmandu Valley - Paudel, Anupama (Nepalese Journal of Business, 2025)
This study examines the consumer satisfaction of internet service providers in Kathmandu Valley. Customer satisfaction is selected as the dependent variable. Similarly, internet speed, technical support, brand image, reliability, security, and pricing are selected as the independent variables. This study is based on primary data with 121 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing customer satisfaction in Kathmandu Valley. The study showed that internet speed has a positive impact on customer satisfaction. It means that an increase in internet speed leads to an increase in customer satisfaction. Similarly, technical support has a positive impact on customer satisfaction. It indicates that an increase in technical support leads to increase in customer satisfaction. Moreover, brand image has a positive impact on customer satisfaction. It means that an improvement in brand image leads to an improvement in consumer satisfaction. Likewise, price has a negative impact on customer satisfaction. It shows that a decrease in price leads to an increase in customer satisfaction. Similarly, pricing has a negative impact on customer satisfaction. It shows that the lower the pricing, the higher would be the customer satisfaction. Further, reliability has a positive impact on customer satisfaction. It shows that the higher the reliability, the higher would be the customer satisfaction. Where security has a positive impact on customer satisfaction. It shows that the higher the security, the higher would be the customer satisfaction.